Poling-free spinning process of manufacturing piezoelectric yarns for textile applications. (5th October 2019) - Park, Sarang; Kwon, Youbin; Sung, Minchang; Lee, Byoung-Sun; Bae, Jihyun; Yu, Woong-Ryeol
Abstract: This report describes a new twist-spinning process for the manufacture of piezoelectric yarn without the need for additional poling processes. Poly(vinylidene fluoride-trifluoroethylene) (PVDF-TrFE) nanofibers were first electrospun and organized into a web structure. Using rotational and translational motors, the nanofibers of the web were pulled and stretched and, finally, twisted into piezoelectric yarns. The crystallinity, β phase ratio, and mechanical and piezoelectric properties of these twist-spun piezoelectric yarns were characterized to assess the effects of the twist-spinning operation on their microstructure and performance. Twist-spun piezoelectric yarns that had undergone high degrees of stretching exhibited enhancements in both crystallinity and β phase ratio by 83% and 12%, respectively. In contrast, high stretching reduced the tensile strength and modulus of the yarns due to small surface angles. The twist-spun piezoelectric yarn with the highest β phase ratio and lowest modulus attained in this study yielded a piezoelectric potential and piezoelectric voltage constant of 500 mV and 0.412 mVm/N, respectively. Graphical abstract: Unlabelled Image Highlights: Poling-free spinning process was designed for piezoelectric nanofiber yarns. PVDF-TrFE nanofibers were enhanced in both crystallinity (by 83%) and β phase ratio (by 12%) after yarn spinning process. Piezoelectric yarn showed high mechanical (tensile strength of 25 MPa) and piezoelectric (potential of 500 mV and g33 of 0.40) properties.